KOINTEGRASI MODEL EKONOMI SEKTOR PERTANIAN INDONESIA (PENDEKTAN VAR DALAM DUAL ECONOMY MODEL) - DARSONO DARSONO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2007)
The indonesian's economy change was very dynamic still in development. Must be carefully for modeling in econometrics. The dual economy model with vector auto-regression (VAR) approach is answer's to sufficiency analytical needed at agricultural sector economic model analysis, so finding the co-integration variables in the modle. the research aim's to composing and comparing between structural VAR and co-integration approach in agricultural sector economic model, and finding the short and long run relation contribution of variables in the model